Gender Differences in Attitude and Barriers to Research by Medical Undergraduate Students in Nigeria - Kenechukwu Franklin Okwunze; Efosa Peace Iyawe; Ifunanya Prosper Agughalam; Aisha Yahya; Priscilla Awoyomi; Emmanuel Metajuwa-kuda; Caroline Anulika Nwamadiegesi; Mayomikun Olawale; Stephen Igwe (University Library System, University of Pittsburgh, 2022)
Background. Medical research, one of the pillars of medical education plays a crucial impact in advancing healthcare by improving the diagnosis, treatment, and prevention of illnesses. It is important to ensure that medical students and early career physicians are involved to research outside the curriculum at an early stage of training. This early involvement has been widely known to increase one's likelihood of building a career in research. In Nigeria, the gender composition of research personnel in universities is alarming as less than a quarter are female. There is a need to describe the factors responsible for this imbalance in order to inform stakeholders on where actionable measures can be taken.   Aim To examine the gender differences in the attitude towards research, willingness to undertake research, and barriers to research reported by undergraduate clinical students in Nigeria.   Methods Six hundred and seventy-two (672) undergraduate medical students in their fourth to sixth years of study in seven selected medical schools across Nigeria completed an electronic survey in August 2022. The survey which was hosted on REDCap was adapted from published works which addressed a similar scope and comprised of 56 items divided into five sections. Gender differences in research experience, willingness to participate in research, attitude towards research and barriers that hinder participation in research were explored using a chi-square test. Variables were collected using a 5-point Likert scale ranging from strongly disagree to agree with a "neutral midpoint" and SPSS version 25 was used in the analysis. Results Although an equal proportion of male and female students reported voluntary involvement in research, 56.2% of male students and 28.8% of female students perceived research as exciting and enjoyable (p<0.001) and 37.5% of male students vs 47.0 of female students perceived research as being complicated.   Male students were more willing to spend more than 3 months on a research project (56.0% vs 42.5%, p<0.001), devote as much time to research as to medical studies (40.1% vs 28%, p=0.002), and to pursue a research-oriented career in the future (49.3% vs 32%, p<0.001). Overall, male students reported a higher number of barriers than female students. However, lack of personal interest in research (19.2% vs 26.9%, male vs female students, p=0.011) and insufficient training in research methodology (70.1% vs 81.7%, male vs female students, p=0.009) were reported more by female students.      Conclusion Although there are no gender differences in the composition of students who report prior voluntarily involvement in research, there are gender differences in the attitude and willingness as well as barriers encountered by clinical students to carry out research.  Tailored measures should be developed around the peculiar barriers expressed by female medical students.